Justiça restaurativa: uma solução humana complementar à justiça retributiva no Direito Penal - Abreu, Milena Cunha de (2024)
This paper presents restorative justice as a new model of justice to be implemented in Brazil, complementing the existing model - retributive justice. Furthermore, in order to reach this conclusion, under the main analysis based on elements of total criminal science, some points are addressed. First, the crisis of the current punitive system is noted, given the failure of the prison system and the failure to achieve the purposes of the custodial sentence, in its entirety. With this, at the same time, it is verified that the victim does not have a fundamental role in the current criminal process, resulting in victimological studies that understand the need for their active participation, so that their rights are guaranteed. With this in mind, it is necessary to adopt a new criminal policy. In this case, this is restorative justice, as a humane and effective way, both to resolve the issue of the crisis of the criminal system and to better repair the damage to the victim, with regard to crimes of lesser potential harm.